2009
DOI: 10.1111/j.1476-5381.2008.00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic and plant‐derived cannabinoid receptor antagonists show hypophagic properties in fasted and non‐fasted mice

Abstract: Background and purpose:Obesity is a severe health problem in the modernized world and understanding the central nervous mechanisms underlying food-seeking behaviour and reward are at the forefront of medical research. Cannabinoid receptors have proven an efficient target to suppress hunger and weight gain by their pharmacological inactivation. Experimental approach: A standard fasted protocol and a novel long-term home-cage observation system with free-feeding animals were used to assess the feeding behaviour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
90
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(101 citation statements)
references
References 54 publications
(78 reference statements)
4
90
2
2
Order By: Relevance
“…Acute intraperitoneal administration of THCV in rodents at 3, 10, and 30 mg/kg body weight caused hypophagia and weight loss, with food intake and body weight returning to normal on day 2 (26). The effect was similar to that of a CB 1 antagonist, AM251, also used in the same study.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…Acute intraperitoneal administration of THCV in rodents at 3, 10, and 30 mg/kg body weight caused hypophagia and weight loss, with food intake and body weight returning to normal on day 2 (26). The effect was similar to that of a CB 1 antagonist, AM251, also used in the same study.…”
supporting
confidence: 55%
“…Rimonabant, a CB 1 receptor antagonist, was the first in its class to be used as antiobesity drug, but led to significant psychiatric AEs (5). Preclinical studies with the plant-derived compound THCV have shown that it produces hypophagia and weight reduction in lean mice (26) and improves glucose tolerance and insulin sensitivity in dietinduced obese mice (27). Similar results have been seen with CBD in ob/ob mice (C.S., unpublished data), and CBD has been reported to lower the incidence of diabetes in nonobese diabetic mice (33) and arrest the onset of autoimmune diabetes in nonobese diabetic mice (34).…”
Section: Discussionmentioning
confidence: 99%
“…-THCV suppresses saccharin palatability and the appetite for sweet taste (736) and, at doses as low as 3 mg/kg, shares the ability of synthetic CB1 antagonists to reduce food intake and body weight gain in mice (726), with potential use in the treatment of obesity (673). However, chronic administration of ⌬ 9 -THCV in animal models of obesity does not modify food intake but produces an early and transient increase in energy expenditure, reduces glucose intolerance in ob/ob mice, and improves insulin resistance in mice with high-fat diet-induced obesity, without consistently affecting plasma lipids.…”
mentioning
confidence: 99%
“…Hau da, funtzionalki Δ 9 -THCVak CB 1 hartzailearen antagonista neutro gisa jokatzen du. Horrela, CB 1 hartzailearen antagonista den AM251 farmakoak bezala, arratoietan jangura inhibi dezake [36] edota rimonabant EKAIA, 31 (2017) Erik Aostri, Joseba Pineda, Aitziber Mendiguren farmakoaren antzera, 6-hidroxidopaminak induzitutako inhibizio motorra murriztu [37]. Dena dela, Δ 9 -THCVak ez ditu CB 1 hartzaileen antagonista klasikoek eragiten duten goitika eta antsietatea sortarazten [38].…”
Section: δ 9 -Tetrahidrokannabibarina In Vitro Ereduetan Eta Animalietanunclassified